A protocol for obtaining upper and lower extremity joints’ range of motion in children using three-dimensional motion analysis system - Afifi, Mohamed; Abdulazeez, Muhammad Uba; Aminian, Kamiar; Stylianides, Georgios Antoniou; Abdullah, Kassim Abdulrahman (Frontiers in Physiology, 2024)
Three-dimensional (3D) motion analysis (MA) techniques are progressively being used in biomechanics research and for clinical applications to assess the risk of injuries. A marker-based 3D MAmotion analysis protocol has been developed to measure the upper and lower extremity joints' active and passive ranges of motion (AROM and PROM) in children. The joints that were included in this protocol are shoulder, elbow, wrist, hip, knee and ankle. The anatomical joint coordinate systems (JCS) have been defined for the upper (UE) and lower (LE) extremities to standardize reporting. A marker placement model was defined according to the International Society of Biomechanics (ISB) recommendations and used to develop the protocol. The proposed movements will bewere captured and analyzed using the Motion Analysis Corporation system integrated with Cortex software. A description of the results is presented for this study to clarify the outcome of the recordings and to highlight the objective of the study. The movements adopted in this study have been selected from various sources to incorporate all joint rotations while ensuring the isolation of each joint motion during the movements. It is recommended that further studies utilize this protocol to draw a relationship between the joints' range of motion (ROM) and the adjacent segments characteristics, i.e., segment length, joint stiffness, etc.